2003
DOI: 10.1523/jneurosci.23-11-04726.2003
|View full text |Cite
|
Sign up to set email alerts
|

Human θ Oscillations Related to Sensorimotor Integration and Spatial Learning

Abstract: oscillations in the rat hippocampus have been implicated in sensorimotor integration (Bland, 1986), especially during exploratory and wayfinding behavior. We propose that human cortical activity coordinates sensory information with a motor plan to guide wayfinding behavior to known goal locations. To test this hypothesis, we analyzed invasive recordings from epileptic patients while they performed a spatially immersive, virtual taxi driver task. Consistent with this hypothesis, we found oscillations during bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
274
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 380 publications
(317 citation statements)
references
References 57 publications
36
274
1
6
Order By: Relevance
“…During navigation, intracranial recordings from depth electrodes in the human hippocampus have shown that theta is more prevalent during movement than during stationary periods (10)(11)(12) and that theta power increases with movement speed (13). In addition, increases in movement-related theta power are seen across the neocortex (10,11,14). These findings support the hypothesis that human theta oscillations might encode self-motion information.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…During navigation, intracranial recordings from depth electrodes in the human hippocampus have shown that theta is more prevalent during movement than during stationary periods (10)(11)(12) and that theta power increases with movement speed (13). In addition, increases in movement-related theta power are seen across the neocortex (10,11,14). These findings support the hypothesis that human theta oscillations might encode self-motion information.…”
mentioning
confidence: 60%
“…Hence, this finding strengthens the translational connection between studies of movement-related theta in human and rodent models. Importantly, this increase in theta power around movement onset may have been overlooked by previous human intracranial recording studies that have exclusively compared pure movement and stationary periods that tend to be of short duration (10)(11)(12)14). Theta power increases are not specific to movement-onset periods, however: Both low and high theta power remained above baseline levels during the remainder of movement in the hippocampus and, to a lesser extent, in the lateral temporal lobe.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Finally, the P episode method (Caplan et al, , 2003Ekstrom et al, 2005) was designed to measure sustained oscillations, and is used after oscillatory power has been computed by another method (typically wavelets- Fig. 1c,f).…”
Section: Specifications Of Analysis Methodsmentioning
confidence: 99%